Effect of consumtion red guava juice to increase hemoglobin levels in pregnant women - Ester Simanullang (Universitas Aisyah Pringsewu, 2022)
One of the indicators based on the sustainable development goals (Sustainable Development Goals / SDGs 2030), is to support welfare and ensure a healthy life for all at all ages with the most important points being to reduce the maternal mortality rate to less than 70 per 100,000 live births and prevent maternal mortality. The death rate for newborns and toddlers is at least 12 per 1000 live births and 25 per 1000 live births for children under five. A study was conducted to determine the effect of giving red guava juice on changes in hemoglobin levels in pregnant women at Praktik Bidan Boloni Tanaka Medan Johor in 2022. In this study the sample used was all pregnant women from March to May as many as 2022 as many as 12 people. . The research showed that in the intervention group before giving red guava juice the majority of moderate anemia with a frequency of 8 respondents (66.7%) and a normal minority with a frequency of 1 respondent (8.3%). Meanwhile, after giving red guava juice the majority were normal with a frequency of 7 respondents (53.8%) and a minority of moderate anemia was one respondent (8.3%). The results of the analysis test in this study using Mann Whitney showed a P-Value of 0.022 (P less than 0.05), namely the effect of giving red guava juice to increase hemoglobin in pregnant women. Pregnant women, especially pregnant women who experience anemia, are expected to regularly consume red guava juice because if consumed properly, red guava juice has many benefits, especially for pregnant women so that it can meet the nutritional needs needed by the body and can maximize absorption of substances iron.Abstrak: Salah satu indikator berdasarkan tujuan pembangunan berkelanjutan (Sustainable Development Goals/SDGs 2030), adalah mendukung kesejahteraan dan menjamin kehidupan yang sehat bagi semua orang di segala usia dengan poin terpenting adalah menurunkan angka kematian ibu menjadi kurang dari 70 per 100.000 kelahiran hidup dan mencegah kematian ibu. Angka kematian bayi baru lahir dan balita minimal 12 per 1000 kelahiran hidup dan 25 per 1000 kelahiran hidup untuk anak balita. Telah dilakukan penelitian untuk mengetahui pengaruh pemberian jus jambu biji merah terhadap perubahan kadar hemoglobin pada ibu hamil di Praktik Bidan Boloni Tanaka Medan Johor tahun 2022. Pada penelitian ini sampel yang digunakan adalah seluruh ibu hamil bulan Maret sampai Mei sebanyak 2022 sebanyak sebanyak 12 orang. . Hasil penelitian menunjukkan bahwa pada kelompok intervensi sebelum pemberian jus jambu biji merah mayoritas anemia sedang dengan frekuensi 8 responden (66,7%) dan minoritas normal dengan frekuensi 1 responden (8,3%). Sedangkan setelah pemberian jus jambu biji merah mayoritas normal dengan frekuensi sebanyak 7 responden (53,8%) dan minoritas anemia sedang sebanyak 1 responden (8,3%). Hasil uji analisis pada penelitian ini dengan menggunakan Mann Whithney menunjukkan P-Value sebesar 0,022 (P kurang dari 0,05) yaitu pengaruh pemberian jus jambu biji merah terhadap peningkatan hemoglobin pada ibu hamil. Ibu hamil khususnya ibu hamil yang mengalami anemia diharapkan untuk rutin mengkonsumsi jus jambu biji merah karena jika dikonsumsi dengan benar, jus jambu biji merah memiliki banyak manfaat terutama bagi ibu hamil sehingga dapat memenuhi kebutuhan nutrisi yang dibutuhkan tubuh dan dapat memaksimalkan penyerapan. dari zat besi.